Sintesis Hidroksiapatit Melalui Precipitated Calcium Carbonate (PCC) Dari Cangkang Kerang Darah Dengan Metode Hidrotermal Pada Variasi Waktu Reaksi Dan Rasio Ca/P - Ichsan, Raja Heru Nur Alam; Helwani, Zuchra; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Potential of waste blood cockle shell in Indonesia is quite large. Waste of blood cockle shell contains calcium carbonate compounds that can be used as raw material for the synthesis of hydroxyapatite . In this research, the PCC synthesis of blood cockle shell in advance to obtain a pure hydroxyapatite. The aim of this research was to get the hydroxyapatite from PCC blood cockle shell, determine optimum process condition and also to investigate the effect of the Ca/P mole ratio and the reaction time toward Hydroxyapatite synthesis. The powder of sea shell was calcined at 900 oC for 2 hours. CaO was converted to PCC which then reacted with diammonium hydrogen phosphate by using water as solvent. The samples then were characterized by using FTIR (Fourier Transform Infrared), XRD (X-Ray Diffraction), and SEM (Scanning Electron Microscopy). The functional groups were observed in the FTIR of the synthesized hydroxyapatite are phosphate (PO43-), hydroxyl (OH-), and carbonate (CO32-). These functional groups indicate that hydroxyapatite has been formed. XRD data showed the main peaks for hydroxyapatite that strenghtened the truth of FTIR characterization. SEM was used to observe the morphology of the synthesized hydroxyapatite that consisted of agglomerates. The optimum conditions in this research is the synthesis of HAp with a ratio of Ca / P 1,61 and 20 hours reaction time with a particle size of hydroxyapatite 39,43 nm, conversion 91,99% and yield 96,66 %.Keywords : Blood cockle shell, Hydroxyapatite, Hydrothermal, Precipitated calcium carbonate